Influence of self-efficacy and peer social support on high school students' motivation to learn mathematics - YC, Waliyati; Lestary, Ira; Amira, Jihan; Sugiarti, Lucia Rini; Suhariadi, Fendy (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to examine the relationship between high school students' self-efficacy and peer support and their willingness to learn mathematics. One of the main issues facing the education sector is the motivation of high school students to comprehend mathematics. Students' willingness to learn mathematics is thought to be significantly impacted by peer social support. 66 high school students participated in the study, which used a quantitative sample technique. Structural equation modeling (SEM) with a non-specific bootstrapping approach was used to evaluate the data. The findings show that self-efficacy has a favorable and significant impact on motivation to learn mathematics (? = 0.669; t = 4.522; p < 0.000). Peer social support significantly and favorably affects kids' motivation to learn math. In summary, peer social support and self-efficacy have a notable and favorable effect on pupils' motivation to learn math. In conclusion, high school students' willingness to learn mathematics is significantly influenced by their peers' social support and their level of confidence. Students' motivation to learn mathematics can be raised by bolstering these two components.